Considerations regarding the most favorite customer clause - Díaz de la Rosa, Angélica (CUADERNOS DE DERECHO TRANSNACIONAL, 2026)
This paper examines a contractual modification clause known as the “most-favoredcustomer clause”. This clause exemplifies the parties’ freedom of contract, aiming to ensure that one party subsequently enjoys more favorable contractual conditions than previously held. This occurs as other parties to the same contracting party, who are also bound by the supplier or promisor of these conditions, experience improvements in their own terms. The improvement of these latter conditions, directly or indirectly, leads to improvements in the conditions of the beneficiary party to the clause. The paper also explores the various ways in which the clause can be invoked and concludes with a brief analysis of its effects.
Keywords: Most-Favoured Customer; Clause automatic modification or contractual renegotiation; Favoured Customer Clause and Competition Law; vertical restraints